Two Balance Measures as Poststroke Predictors of Ambulation Status at Discharge From Inpatient Rehabilitation. Issue 3 (13th July 2022) - Berry, Olivia; Voigtmann, Christina; Curran, Christopher; Dawson, Nicole; Dominguez, Jose; Beato, Morris
Abstract : Purpose: Early predictors of the degree of walking ability poststroke are vital considering the decreased length of stay in most inpatient rehabilitation facilities (IRFs). Prediction of functional walking capability upon discharge from IRFs requires more investigation. This study aimed to (1) determine whether the Postural Assessment Scale for Stroke (PASS) and the Berg Balance Scale (BBS) can predict an individual's IRF discharge poststroke gait category and (2) establish cut-off scores for these assessments to better forecast gait category upon discharge. Methods: A total of 180 individuals with an admitting stroke diagnosis were assessed with both balance measures and the 10-m walking test at admission and discharge from inpatient rehabilitation. Participants were stratified by gait speed into 4 groups (nonambulators: 0 m/s; household ambulators: <0.4 m/s; limited community ambulators: 0.4-0.8 m/s; and community ambulators: >0.8 m/s). Results: Both the admission PASS and the BBS scores may predict patients who will be ambulatory and performed similarly in differentiating between gait classifications upon discharge from inpatient rehabilitation ( P < .01). Cut-off scores of 6 or less on the BBS (sensitivity 96%; specificity 83%) and 17 on the PASS (sensitivity 92%; specificity 90%) were established to predict nonambulators, and cut-off scores of 29 or more on the BBS (sensitivity 92%; specificity 86%) and 30 on the PASS (sensitivity 80%; specificity 87%) were established to predict community ambulators. Conclusions: These results can inform clinicians of poststroke patients' walking prognosis and advise discharge needs early in a patient's IRF stay.